2002
DOI: 10.1093/nar/gkf618
|View full text |Cite
|
Sign up to set email alerts
|

Human DNA glycosylases of the bacterial Fpg/MutM superfamily: an alternative pathway for the repair of 8-oxoguanine and other oxidation products in DNA

Abstract: The mild phenotype associated with targeted disruption of the mouse OGG1 and NTH1 genes has been attributed to the existence of back-up activities and/or alternative pathways for the removal of oxidised DNA bases. We have characterised two new genes in human cells that encode DNA glycosylases, homologous to the bacterial Fpg (MutM)/Nei class of enzymes, capable of removing lesions that are substrates for both hOGG1 and hNTH1. One gene, designated HFPG1, showed ubiquitous expression in all tissues examined wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
239
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 261 publications
(258 citation statements)
references
References 59 publications
18
239
0
Order By: Relevance
“…In contrast, the suppression of the mutations by 8-oxo-Gua by NTH1 and NEIL1 has come under scrutiny lately, due to their lack of activity and weak activity, respectively, for DNA duplexes containing 8-oxo-Gua:C [39, [41][42][43][44]. The findings reported herein provides the first evidence to demonstrate that NTH1 and NEIL1 suppress the mutagenesis induced by 8-oxo-Gua in living cells.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In contrast, the suppression of the mutations by 8-oxo-Gua by NTH1 and NEIL1 has come under scrutiny lately, due to their lack of activity and weak activity, respectively, for DNA duplexes containing 8-oxo-Gua:C [39, [41][42][43][44]. The findings reported herein provides the first evidence to demonstrate that NTH1 and NEIL1 suppress the mutagenesis induced by 8-oxo-Gua in living cells.…”
Section: Discussionmentioning
confidence: 84%
“…NEIL1 has the ability to excise not only 8-oxo-Gua in ds DNA [39,[41][42][43] but also 8-oxo-Gua in ss DNA [44]. In addition, proliferating cell nuclear antigen (PCNA) interacts with NEIL1 and stimulates NEIL1 activity with respect to excising 5-hydroxyuracil from ss DNA sequences, including fork structures [55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, NEIL1 was later shown to prefer ring-opened purines, i.e., formamidopyrimidine (Fapy)-A and -G, which along with 8-oxoG are the preferred substrates for E. coli Fpg. While we initially showed 8-oxoG as a poor substrate of NEILs on duplex DNA substrate, others have shown NEIL1's robust 8-oxoG excision activity [54,56]. Subsequently, we showed that NEILs' activity and substrate specificity depend largely on the DNA structure, and NEILs have significant 5-hydroxyuracil excision activity towards single-stranded or bubble DNA [57].…”
Section: Mammalian Dna Glycosylases For Oxidized Basesmentioning
confidence: 79%
“…Thus, both NTH1, preferring oxidized pyrimidines as substrates, and OGG1, primarily responsible for the removal of 8-oxoG and ring opened guanine, i.e., formamidopyrimidine (Fapy-G), catalyze β elimination [11,49]. Subsequently, we characterized two additional human DNA glycosylases (also independently discovered by others), which belong to the Fpg/Nei family; we named these NEIL1 and NEIL2 [50][51][52][53][54][55]. All these enzymes as already indicated are bifunctional glycosylases with broad substrate range.…”
Section: Mammalian Dna Glycosylases For Oxidized Basesmentioning
confidence: 99%